EVALUATION OF ASSISTANCE TOOLS FOR DIAGNOSIS OF DISEASES BY APPROACHING TO PERSONALIZED MEDICINE ON METAGENOMIC DATA - Phan Tấn Tài; Tạ Đặng Vĩnh Phúc; Phan Nguyễn Minh Thảo; Nguyễn Thị Ngọc Chăm; Đào Công Tính; Phạm Huỳnh Ngọc; Nguyễn Thanh Hải (Tạp chí Khoa học Đại học Đà Lạt)
In recent years, Metagenomic data, or “multi-genome” data, has been increasingly used for research in “personalized medicine” approaches with the purpose of improving and enhancing effectiveness in human health care. Many studies have experimentally analyzed this data and proposed many methods to improve the accuracy of the analysis. Applying and integrating information technology to process and analyze Metagenomic data for personalized medicine approaches are necessary because of the enormous complexity of Metagenomic data. The potential advantages of Metagenomic data have been proven through many studies. Within the scope of this research, we introduce and evaluate useful tools for studying Metagenomic data in supporting the diagnosis of human disease and health conditions. From these studies, we may develop extensive and in-depth studies from previous studies to explore the important effect of the microbial ecosystem that is a rich set of microbial features for prediction and biomarker discovery in the human body. Moreover, there are trends diagnosis, appropriate treatments to improve and enhance human health.